2022
DOI: 10.1101/2022.05.23.493121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-chemokine antibodies after SARS-CoV-2 infection correlate with favorable disease course

Abstract: Infection by SARS-CoV-2 leads to diverse symptoms, which can persist for months. While antiviral antibodies are protective, those targeting interferons and other immune factors are associated with adverse COVID-19 outcomes. Instead, we discovered that antibodies against specific chemokines are omnipresent after COVID-19, associated with favorable disease, and predictive of lack of long COVID symptoms at one year post infection. Anti-chemokine antibodies are present also in HIV-1 and autoimmune disorders, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Combination therapy with CXCL8-CXCR1/ CXCR2 inhibitors may provide further benefit in cancer treatment [112,113] CXCL8 production by endothelial colony-forming cells might contribute to neutrophil infiltration in idiopathic pulmonary fibrosis [133] Neutrophils in inflamed joints of juvenile idiopathic arthritis (JIA) patients display a hyperactivated phenotype. A complex intertwining between innate and adaptive immunity probably drives JIA [142] CXCL8-CXCR1/CXCR2 may induce podocyte damage in type 2 diabetic kidney disease [160] Mucosal CD14 + monocyte-like cells induced CXCL8 in colonic memory CD4 + T-lymphocytes, showing crosstalk between innate and adaptive immunity in ulcerative colitis [165] Key role for CXCL8 & neutrophils in the pathogenesis of severe COVID-19, with improvements in clinical outcomes of patients treated with a CXCR1/CXCR2 antagonist [166,168,169,187] Anti-CXCL8 autoantibodies might reduce the severe systemic inflammation associated with neutrophil activation in COVID-19 [170] Blocking CXCR1/CXCR2 signaling reduced NET formation, tissue injury & mortality without impairing bacterial clearance in septic mice [171] inflammation by binding, internalization, and transport of CXCL8 and other chemokines from the basolateral toward the apical side of endothelial cells, which facilitates immobilization and presentation to leukocytes promoting their extravasation [44]. GAGs probably participate in this chemokine transcytosis process as well (Fig.…”
Section: Structure and Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination therapy with CXCL8-CXCR1/ CXCR2 inhibitors may provide further benefit in cancer treatment [112,113] CXCL8 production by endothelial colony-forming cells might contribute to neutrophil infiltration in idiopathic pulmonary fibrosis [133] Neutrophils in inflamed joints of juvenile idiopathic arthritis (JIA) patients display a hyperactivated phenotype. A complex intertwining between innate and adaptive immunity probably drives JIA [142] CXCL8-CXCR1/CXCR2 may induce podocyte damage in type 2 diabetic kidney disease [160] Mucosal CD14 + monocyte-like cells induced CXCL8 in colonic memory CD4 + T-lymphocytes, showing crosstalk between innate and adaptive immunity in ulcerative colitis [165] Key role for CXCL8 & neutrophils in the pathogenesis of severe COVID-19, with improvements in clinical outcomes of patients treated with a CXCR1/CXCR2 antagonist [166,168,169,187] Anti-CXCL8 autoantibodies might reduce the severe systemic inflammation associated with neutrophil activation in COVID-19 [170] Blocking CXCR1/CXCR2 signaling reduced NET formation, tissue injury & mortality without impairing bacterial clearance in septic mice [171] inflammation by binding, internalization, and transport of CXCL8 and other chemokines from the basolateral toward the apical side of endothelial cells, which facilitates immobilization and presentation to leukocytes promoting their extravasation [44]. GAGs probably participate in this chemokine transcytosis process as well (Fig.…”
Section: Structure and Expressionmentioning
confidence: 99%
“…Recently, it was demonstrated that anti-chemokine antibodies are associated with a positive outcome in COVID-19 and are predictive for a lack of long COVID symptoms. As such, these antibodies may play an anti-inflammatory role by reducing the damaging inflammatory response associated with neutrophil activation and severe COVID-19 [170].…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…We found our set of differentially regulated chemokines (CCL8, CCL19 and CCL25) intriguing because autoantibodies against CCL8 are augmented in long-term convalescent COVID-19 individuals, and elevated antibodies against the COVID-19 signature chemokine CCL19 46 are documented with high confidence in both acute and long-term COVID-19 phases compared to uninfected controls 49 . Interestingly, autoantibodies against CCL25 are augmented in mild COVID-19 patients compared to those requiring hospitalization 49 . Convalescents exhibiting PASC at 12 months have a significantly lower cumulative level of anti-chemokine antibodies at six months compared to those who reported no PASC 49 .…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, autoantibodies against CCL25 are augmented in mild COVID-19 patients compared to those requiring hospitalization 49 . Convalescents exhibiting PASC at 12 months have a significantly lower cumulative level of anti-chemokine antibodies at six months compared to those who reported no PASC 49 . In our STRING protein-protein analysis of significantly regulated analytes at week 1, we found strong interactions between CCL8, CCL19, CCL25, TNF and IL-18 confirming a link between this chemokine signature and inflammatory responses in our infected AGM model, likely contributing to early adverse and long-term pathological events.…”
Section: Discussionmentioning
confidence: 98%
“…and CCL25) intriguing because autoantibodies against CCL8 are augmented in long-term convalescent COVID-19 individuals, and elevated antibodies against the COVID-19 signature chemokine CCL19 46 are documented with high confidence in both acute and long-term COVID-19 phases compared to uninfected controls 49 . Interestingly, autoantibodies against CCL25 are augmented in mild COVID-19 patients compared to those requiring hospitalization 49 . Convalescents exhibiting PASC at 12 months have a significantly lower cumulative level of anti-chemokine antibodies at six months compared to those who reported no PASC 49 .…”
Section: Discussionmentioning
confidence: 99%